(untitled) (ENTHYMEMA, 2012)
This contribution aims to shed a light on the importance of Bakhtin’s thought and theory of the character for the definition of a «contemporary humanism» and for its further developments. In particular, we will refer – without in any way claiming to be exhaustive –to novels by Michel Houellebecq, John M. Coetzee, Philip Roth, Javier Marías. Starting from some bakhtinian concepts like the dialogism and the extra-locality, we will analyze the forms of inter-textuality, the modes of irony and paradox, and the symbology of death as collocation of the character at the ultimate threshold.